Substrate temperature dependent studies on properties of chemical spray pyrolysis deposited CdS thin films for solar cell applications *Project supported by the Department of Science and Technology (DST), Ministry of New and Renewable Energy (MNRE), Government of India, New Delhi. (February 2017) - Diwate, Kiran; Pawbake, Amit; Rondiya, Sachin; Kulkarni, Rupali; Waykar, Ravi; Jadhavar, Ashok; Rokade, Avinash; Funde, Adinath; Mohite, Kakasaheb; Shinde, Manish; Pathan, Habib; Devan, Rupesh; et al.
Abstract: Thin films of CdS have been prepared by chemical spray pyrolysis by spraying precursor solution directly onto soda lime glass (SLG) substrates. Influence of substrate temperature on structural, optical, morphological and electrical properties have been investigated by using various techniques such as low angle X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), transmission electron microscopy (TEM), UV–visible spectroscopy photoluminescence (PL) spectroscopy etc. Formation of CdS has been confirmed by low angle XRD, Raman spectroscopy and XPS analysis. XRD pattern showed that CdS films are polycrystalline, have hexagonal structure and prefer orientation of crystallites shifts from (101) to (002) with increase in substrate temperature. Raman spectroscopy revealed that exciton-phonon coupling depends on substrate temperature and hence on crystallite size. Optical band gap increased from 2.43 to 2.99 eV when substrate temperature increased from 325 to 475 ° C . Transmittance of the film also showed an increasing trend from ∼ 52 % to ∼ 80 % with increase in substrate temperature. Such high band gap and transmittance values of CdS films prepared at 475 ° C make it a useful window material in CdS/CdTe and CdS/Cu2 S heterojunction solar cells.